The War in Ukraine, Agricultural Trade and Risks to Global Food Security - Thomas Glauben; Miranda Svanidze; Linde Götz; Sören Prehn; Tinoush Jamali Jaghdani; Ivan urić; Lena Kuhn (Intereconomics, 2022)
Any calls to move towards a centrally planned economy or autarky are strongly advised against, as this would only be to the detriment of food security in the Global South.
Keywords: Q13; Q17; Q18; 330